Dynamic Correlation between Whisking and Breathing Rhythms in Mice - Cao, Ying (Society for Neuroscience, 2012)
Sniffing, a high-frequency, highly rhythmic inhalation and exhalation of air through the nose, plays an important role in rodent olfaction. Similarly, whisking, the active rhythmic movement of whiskers, plays an important role in rodent tactile sensation. Rodents whisk and sniff during exploratory behavior to sample odorants and surfaces. Whisking is thought to be coordinated with sniffing and normal respiratory behavior, but the precise temporal relationships between these movements are not known. Here, using direct measurements of whisking and respiratory movements, we examined the strength and temporal dynamics of the correlation between large-amplitude whisker movements and respiratory rhythm in mice. Whisking movements were detected using an optical sensor, and respiration was monitored with a thermistor placed close to the nostril. Our measurements revealed that breathing and whisking movements were significantly correlated only when the whisking rhythm was <5 Hz. Only a fraction (∼13%) of all large-amplitude whisker movements occurred during episodes of high-frequency (>5 Hz) respiration typically associated with sniffing. Our results show that that the rhythms of respiratory and whisking movements are correlated only during low-frequency whisking and respiration. High-frequency whisking and sniffing behaviors are not correlated. We conclude that whisking and respiratory rhythms are generated by independent pattern-generating mechanisms.